2011
DOI: 10.1038/cr.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Association of telomere length with authentic pluripotency of ES/iPS cells

Abstract: Telomerase and telomeres are important for indefinite replication of stem cells. Recently, telomeres of somatic cells were found to be reprogrammed to elongate in induced pluripotent stem cells (iPSCs). The role of telomeres in developmental pluripotency in vivo of embryonic stem cells (ESCs) or iPSCs, however, has not been directly addressed. We show that ESCs with long telomeres exhibit authentic developmental pluripotency, as evidenced by generation of complete ESC pups as well as germline-competent chimera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(179 citation statements)
references
References 56 publications
5
173
0
1
Order By: Relevance
“…These findings may also partially explain why NT can faithfully reprogram somatic cells into ES cells [5,8,20,21,42]. In contrast, during somatic reprogramming induced by the Yamanaka factors, telomere elongation is primarily mediated by telomerase [59,60]. Endogenous Zscan4 is not activated during the early stages of reprogramming induced by OKSM or OSK, as shown in our study (Supplementary information, Figure S1F) and in other report [38], further supporting the hypothesis that telomerase activity is the primary mechanism of telomere re-elongation regulation during OSKM-or OSK-mediated reprogramming.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These findings may also partially explain why NT can faithfully reprogram somatic cells into ES cells [5,8,20,21,42]. In contrast, during somatic reprogramming induced by the Yamanaka factors, telomere elongation is primarily mediated by telomerase [59,60]. Endogenous Zscan4 is not activated during the early stages of reprogramming induced by OKSM or OSK, as shown in our study (Supplementary information, Figure S1F) and in other report [38], further supporting the hypothesis that telomerase activity is the primary mechanism of telomere re-elongation regulation during OSKM-or OSK-mediated reprogramming.…”
Section: Discussionmentioning
confidence: 87%
“…Feeder cells were generated by irradiating ICR MEFs. MEFs were derived from E13.5 embryos of C57BL/6 mice that were heterozygous for the Oct4-GFP transgenic allele, as previously described [60,62]. In this study, we used MEFs within the first three passages for iPS cell generation to avoid replicative senescence.…”
Section: Cell Culturementioning
confidence: 99%
“…ES cells additionally have high activity of telomerase, the enzyme involved in de novo generation of telomeres, which, together with the accessibility of telomeric regions, means that ES cells have longer telomeres than somatic cells. The length of telomeres has been directly associated with functional potency as ES cells with short telomeres show a decreased functional potency in chimaera and teratomas assays [67]. Both Wnt signalling and the pluripotency-associated factor Klf4 regulate the expression of telomerase reverse transcriptase (Tert), a catalytic subunit of telomerase.…”
Section: Chromatin States and Totipotencymentioning
confidence: 99%
“…Tetraploid embryo complementation experiments have shown that telomerase-deficient mESCs with short telomeres lose their ability to generate complete ESC-pups (Huang et al, 2011). In contrast, induced pluripotent stem cells (iPSC), which resemble ESCs in many ways, with long telomeres, generate chimeras at a higher efficiency than those with shorter telomeres (Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our current knowledge of telomere maintenance in ESCs is largely derived from studies in mouse ESCs (mESCs): telomere elongation has been observed during in vitro derivation of mESCs (Varela et al, 2011); loss of telomerase activity in mESCs resulted in progressive telomere loss, genomic instability, aneuploidy and telomere fusion, eventually leading to reduced growth rates (Niida et al, 1998); telomerase overexpression enhanced self-renewal, improved resistance to apoptosis and increased proliferation in mESCs (Armstrong et al, 2005). Tetraploid embryo complementation experiments have shown that telomerase-deficient mESCs with short telomeres lose their ability to generate complete ESC-pups (Huang et al, 2011). In contrast, induced pluripotent stem cells (iPSC), which resemble ESCs in many ways, with long telomeres, generate chimeras at a higher efficiency than those with shorter telomeres (Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%